Late Jurassic event of ignimbrite flare-up linked to extensional tectonics: The beginnings of Andean volcanism in southern Patagonia (~46°S, Chile). - Suárez, Rodrigo Javier (2024)
Fil: Suárez, Rodrigo Javier. Universidad Nacional de Río Negro, Instituto de Investigación en Paleobiología y Geología, Río Negro, Argentina